Performance and Prospects of Wheat Market Outlook in India - Bisen, Jaiprakash; Kumar, Shiv; Singh, Dharam Raj; Nain, Manjeet Singh; Arya, Prawin; Tiwari, Utkarsh (Indian Journal of Extension Education, 2022)
The study used secondary data on wheat demand and supply and assessed its market performance (1980-2019). Additionally, it compared the market outlook of wheat for 2020-30. The study reported that the wheat supply and demand increased by 3.14 and 2.71 times, respectively, from 1980 to 2020. Production and food demand contributed about 90 per cent each to the supply and demand growth. Spatially, the west, north and east zones remained the primary contributor (>95%) to the market supply of wheat. West zone performed better in area (1.32%) and production growth (3.82%), while the north zone registered highest yield growth of 2.8 t/ha during last 40 years. The same period registered a growth of 9.69 per cent in the net trade of wheat. On the demand side, although the per capita consumption of wheat registered a negative growth (-1.45%), the food demand grew by 2.51 per cent per annum in the past four decades. Market outlook of wheat suggested that the wheat surplus during 2020-30 would be between -3.4 to 32 million tonnes with an average of 20 million tonnes.
Keywords: Market outlook; Demand and supply; Wheat; Food demand; Food production system